An assessment of silver copper sulfides for photovoltaic applications: theoretical and experimental insights. Issue 32 (1st August 2016) - Savory, Christopher N.; Ganose, Alex M.; Travis, Will; Atri, Ria S.; Palgrave, Robert G.; Scanlon, David O.
Abstract : As the worldwide demand for energy increases, low-cost solar cells are being looked to as a solution for the future. Abstract : As the worldwide demand for energy increases, low-cost solar cells are being looked to as a solution for the future. To attain this, non-toxic earth-abundant materials are crucial, however cell efficiencies for current materials are limited in many cases. In this article, we examine the two silver copper sulfides AgCuS and Ag3 CuS2 as possible solar absorbers using hybrid density functional theory, diffuse reflectance spectroscopy, XPS and Hall effect measurements. We show that both compounds demonstrate promising electronic structures and band gaps for high theoretical efficiency solar cells, based on Shockley–Queisser limits. Detailed analysis of their optical properties, however, indicates that only AgCuS should be of interest for PV applications, with a high theoretical efficiency. From this, we also calculate the band alignment of AgCuS against various buffer layers to aid in future device construction.